MORPHOFUNCTIONAL PROPERTIES OF THE SPLEEN OF WHITE RATS IN POSTNATAL ONTOGENESIS - Turdiyev M.R. (DEVELOPMENT OF EDUCATION AND SCIENCE IN THE ERA OF DIGITAL TRANSFORMATION, 2025)
Annotation research related to the period of white rats of postnatal age talog'idagi ontogenez morphological, and functional changes morfometrik were analyzed. The results obtained in the analysis, the mass of the spleen index, the linear dimensions, the relative area of the red and white pulp, white pulp of the configuration of specific features in different periods of postnatal age indicators morfometrik ontogenez. The results of this research to the development of the immune system of laboratory animals depend on the age of qonuniyat studying, as well as plays an important role in the development of criteria for experimental studies morfofunktsional.